Laku Pancawisaya: Ajaran Tokoh Wayang Semar dalam Mereduksi Krisis (Jurusan Bimbingan dan Konseling Islam, 2020)
This article aims to describe what is the pancawisaya practice and what values it contains, and how Pancawisaya practice to reduct the problem of crises. Pancawisaya practice is a teaching that contains a reflection of the wisdom of life that was taught by Semar to Arjuna after the death of his father, Prabu Pandu Dewanata. Semar is a representation of a problem solver or crisis counselor because he is a protector and guidance officer, and has a noble personality. Pancawisaya practice contains philosophical and mystical values as is the practice of Javanese figures in general who love to mystical. Examining from soul processing contains similarities with the value of Sufistic / Sufism akhlaqi. Examining the concept of behavior in getting happiness contains similarities to the concepts of Aristotales, Socrates, Plato, Pythagoras and several other Muslim philosophers, such as al-Faraby, Ibn Miskawayh, al-Haytam, al-Ghazali. Pancawisaya practice to reduct the problem of crises teaches optimism in action. To resolve a crisis situation, humans must return to the meaning of life from the results of managed positive thoughts. Positive thoughts are formed through the Sufistic experience that is carried out; in the form of meditation, meditation, or seclusion.